MANAGEMENT OF MAJOR DISEASES OF RICE THROUGH NATIVE BIOCONTROL AGENT (Journal of Plant Disease Sciences, 2017)
Evaluation of different application methods of native Pseudomonas fluorescens against major diseases of rice was carried out during five consecutive seasons of 2012-13, 2013, 2013-14, 2014 and 2014- Rabi Kharif Rabi Kharif Rabi 15 at Rice Research Station, Moncompu, Alappuzha. The diseases including sheath blight, blast, bacterial blight and brown spot of rice.The treatments were seed + Pf seedling dip, seed + soil, seed + seedling + foliar and seed + soil + foliar Pf Pf Pf spray with the standard check fungicide carbendazim.Seed + soil and seed + seedling dip treatments were performed well in reducing the disease severity and visual score. The pooled data of five seasons showed that the native bioformulation Pseudomonas fluorescens as seed + seedling dip or seed + soil application was found superior compared to seed + seedling dip + foliar and seed + soil + foliar application treatment for the effective management of sheath blight, blast, bacterial blight and brown spot disease occurrence in different region of Kuttanad.
Keywords: Rice, sheath blight, blast, bacterial blight, brown spot, Pseudomonas fluorescens.